Randomized Controlled Trial of Paper-Based at a Hospital versus Continual Electronic Patient-Reported Outcomes at Home for Metastatic Cancer Patients: Does Electronic Measurement at Home Detect Patients' Health Status in Greater Detail?. (January 2022) - Shiroiwa, Takeru; Hagiwara, Yasuhiro; Taira, Naruto; Kawahara, Takuya; Konomura, Keiko; Iwamoto, Tetsuya; Noto, Shinichi; Fukuda, Takashi; Shimozuma, Kojiro
Purpose: This study aimed to determine whether continual electronic patient-reported outcome (ePRO) measurements at home can capture the fluctuations in health-related quality of life (HRQOL) scores between visits. Methods: We performed a randomized controlled trial to compare the scores obtained by standard practice (paper-based measurements in the hospital) to scores by continuous measurement of ePRO at home. Metastatic cancer patients were randomly assigned to either the paper-based ( n = 50) or the ePRO group ( n = 52). EQ-5D-5L and EORTC QLQ C-30 scores were obtained on 3 different chemotherapy days in the paper-based group. Meanwhile, scores were obtained on the chemotherapy day and on days 3, 7, 10, and 14 in the ePRO group during 2 cycles. The first hypothesis of our study was that both scores at the same time points would be equivalent despite different measurement frequency, place, or mode of measurement. The second hypothesis was that PRO score–adjusted time would be different between the groups. For equivalence, the endpoint was the mean EQ-5D-5L index value on the chemotherapy day before the outpatient treatment. Only if equivalence was shown, quality-adjusted life-days (QALDs) were considered using all the data. Results: The adjusted mean difference in the EQ-5D-5L index was determined to be −0.013 (95% confidence interval [CI]: −0.049 to 0.022); the 95% CI did not exceed the equivalence margin. Similarly, the mean difference in global health status (2.28 [95% CI: −2.55 to 7.11]) also showed equivalence. However, the QALD by EQ-5D-5L was significantly lower in the ePRO group by 1.36 per 30 d (95% CI: −2.22 to −0.51; P = 0.0021). Conclusions: Continual measurements of the HRQOL at home by ePRO may yield more detailed profiles of the HRQOL.